2018
DOI: 10.3390/coatings8120426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PTFE Particle Size on Superhydrophobic Coating for Supercooled Water Prevention

Abstract: Polytetrafluoroethylene (PTFE) chemically repels water droplets due to the nature of fluorine substituents. This paper presents an experimental study on the impact of PTFE particle size and temperature on the hydrophobicity of a surface. The present study analyzes hydrophobicity due to both the chemical properties of PTFE and the microstructure created by PTFE particles. Herein, studies of the contact angle and the sliding angle of these surfaces are described in supercooled-water conditions ranging from −10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In this work, a superhydrophobic coating was created through modification of an existing PTFE coating [19]. The components of the polymer were PTFE nanoparticles from Millipore Sigma binding and hardening agents from ShinEtsu, and a dispersant from 3M.…”
Section: Methods and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, a superhydrophobic coating was created through modification of an existing PTFE coating [19]. The components of the polymer were PTFE nanoparticles from Millipore Sigma binding and hardening agents from ShinEtsu, and a dispersant from 3M.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…The contact and roll-off angle tests were performed at 20 °C. Because both contact and roll-off angle tests were used to measure hydrophobic performance, the droplets did not need to be supercooled, as Morita et al have demonstrated that temperature has negligible impact on the hydrophobicity of a surface [19]. For water at the length scale used, droplet size has minimal impact on contact angle [21].…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…A solid surface is referred to as superhydrophobic [6] when its contact angle is higher than 150 • and its contact angle hysteresis is lower than 10 • (low shear adhesion). These low-adhesion surfaces reveal different properties such as self-cleaning [7,8] or anti-icing [9,10]. We postulate that water repellency might enhance the release performance of fluoropolymer coatings [11].…”
Section: Introductionmentioning
confidence: 94%
“…Some previous works demonstrated that both the polytetrafluoroethylene (PTFE) particle size [10] and the morphology of the fluoropolymer contact surface have a direct influence on the water repellency properties offered by the coating. In the case of PTFE coatings, a microscopic surface morphology in which spherical nanoparticles have been produced is able to present contact angle values greater than 140 • [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at low water content, the silica nanoparticles initially form oligomers with small network size, aggregate and grow with each other to form a network structure with a high crosslinking degree [26]. According to Morita et al [27] an increase of particle size, could decrease the total area of interaction between the fluids and solid surface. It results in lower energy required to remove a droplet, and thus, it increases the hydrophobicity of the surface.…”
Section: -3-particle Size Analysismentioning
confidence: 99%